Assessing the effects of a mixed Eimeria spp. challenge on performance, intestinal integrity, and the gut microbiome of broiler chickens - Graham, Danielle; Petrone-Garcia, Victor M.; Hernandez-Velasco, Xochitl; Coles, Makenly E.; Juarez-Estrada, Marco A.; Latorre, Juan D.; Chai, Jianmin; Shouse, Stephanie; Zhao, Jiangchao; Forga, Aaron J.; Senas-Cuesta, Roberto; Laverty, Lauren; et al. (Frontiers in Veterinary Science, 2023)
A mixed Eimeria spp. challenge model was designed to assess the effects of challenge on broiler chicken performance, intestinal integrity, and the gut microbiome for future use to evaluate alternative strategies for controlling coccidiosis in broiler chickens. The experimental design involved broiler chickens divided into two groups: a control group (uninfected) and a positive control group, infected with E. acervulina (EA), E. maxima (EM), and E. tenella (ET). At day-of-hatch, 240 off-sex male broiler chicks were randomized and allocated to one of two treatment groups. The treatment groups included: 1) Non-challenged (NC, n=5 replicate pens); and 2) challenged control (PC, n=7 replicate pens) with 20 chickens/pen. Pen weights were recorded at d0, d16, d31, d42, and d52 to determine average body weight (BW) and (BWG). Feed intake was measured at d16, d31, d42, and d52 to calculate feed conversion ratio (FCR). Four diet phases included a starter d0-16, grower d16-31, finisher d31-42, and withdrawal d42-52 diet. At d18, chickens were orally challenged with 200 EA, 3,000 EM, and 500 ET sporulated oocysts/chicken. At d24 (6d post-challenge) and d37 (19d post-challenge), intestinal lesion scores were recorded. Additionally, at d24, FITC-d was used as a biomarker to evaluate intestinal permeability and ileal tissue sections were collected for histopathology and gene expression of tight junction proteins. Ileal and cecal contents were also collected to assess the impact of challenge on the microbiome. BWG and FCR from d16-31 was significantly (P<0.05) reduced in PC compared to NC. At d24, intestinal lesion scores were markedly higher in the PC compared to the NC. Intestinal permeability was significantly increased in the PC group based on serum FITC-d levels. Cadherin 1 (CDH1), calprotectin (CALPR), and connexin 45 (Cx45) expression was also upregulated in the ileum of the PC group at d24 (6d post-challenge) while villin 1 (VIL1) was downregulated in the ileum of the PC group. Additionally, Clostridium perfringens (ASV1) was enriched in the cecal content of the PC group. This model could be used to assess the effect of alternative coccidiosis control methods during the post-challenge with EA, EM, and ET.